Gestión financiera en la Municipalidad Provincial de Maynas periodo 2023 - Vargas Gomez, Ana Paola (2025)
The objective of this research was to evaluate the Financial Management of the Provincial Municipality of Maynas for the 2023 period. The study followed a quantitative approach with a non-experimental research design, using a cross-sectional type of design and a descriptive scope. The population and sample consisted of all financial and budgetary information of the Provincial Municipality of Maynas during the 2023 period. A documentary analysis guide was used as the data collection instrument. The research concluded that the Provincial Municipality of Maynas shows a significant dependency on external transfers, as only 10% of its resources come from self-generated revenues, and 17% of total income is generated through local taxes. This reflects a limited capacity to generate autonomous resources. Furthermore, a current liquidity ratio of 2.60 indicates that for every sol of current liabilities, the Municipality has 2.60 soles in current assets to cover these obligations. Additionally, a total liquidity ratio of 8.06 shows that for every sol of total liabilities (current and non current), the Municipality has 8.06 soles in total assets to meet its obligations. Therefore, the Municipality demonstrates a strong capacity to meet both short- and long-term obligations, ensuring financial stability. Additionally, the income execution rate (96%) and expenditure efficiency rate (84%) indicate reasonable performance in budget management, although there is room for improvement in planning and execution.